Analisis Pelaksanaan Pekerjaan Slab Track Light Rail Transit Sumatera Selatan - Lestari, Sachiko Mawaddah; Fauzan, Muhammad (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2017)
Transportation has an important role in supporting economic growth, development and unifying the territory of the Unitary Republic of Indonesia, in order to improve transportation services in supporting development in South Sumatra Province, and supporting the implementation of the 2018 Asian Games, it is necessary to accelerate the implementation of Light Rail Transit in the province of South Sumatra. This is related to the Republic of Indonesia's Presidential Regulation Number 116 of 2015 concerning the Acceleration of the Operation of Light Rail Transit in South Sumatra Province. At the railroad track in Indonesia there is currently no railroad that has operated using the slab track construction but at this time the Government of Indonesia is conducting railroad construction in Indonesia on a national scale. In the construction of the South Sumatra LRT (Light Rail Transit) is a power railroad construction electricity that is in the process of development that will use modern railroad construction that is using slab track construction. In this very happy opportunity the writer got the opportunity to do research at the South Sumatra LRT Work Unit because the South Sumatra LRT is under construction. South Sumatra LRT uses elevated road construction using slab track construction. At present the South Sumatra LRT is the first project to undertake slab track construction in Indonesia. In fact, there is no railroad in Indonesia that operates using slab track construction.